Kebahagiaan dalam Perspektif Kebudayaan Jawa: Kajian Terhadap Teks Wulang Utami Tigang Prakawis - Wahyuni Anggita Sari; Munawar Holil (Perpustakaan Nasional RI, 2023)
This study examines the text of Wulang Utami Tigang Prakawis (WUTP). WUTP is a manuscript collection of National Library of Indonesia with the collection code, NB 816. One of the three teachings of WUTP discusses on happiness. Happiness was chosen because all of the teachings in the WUTP text are related to it. However, happiness has different meaning depends on the culture. The main problem in this study is how is happiness based on the WUTP text? The purpose of this study is to find out happiness in the perspective of Javanese culture which is stated in the WUTP text. Qualitative study is applied in this study with the use of philological work methods and the needs theory by Abraham Maslow. The results indicate that: (1) Happiness is a main thing, well-known, achieveable, and has relationship with needs. (2) Maslow's hierarchy of needs can be achieved by fulfilling the happiness factors in the WUTP text, and (3) Happiness in the WUTP text is an ideal picture of happiness in the first half of the 20th century. Based on the results, it can be states that the WUTP text is an ideology that interprets happiness as relating to basic human needs.